What Remains to Be Discovered? - Nováček , Pavel (Studia Ecologiae et Bioethicae, 2021)
What major scientific breakthroughs will occur in the rest of the 21st century? We can hardly imagine what discoveries await us in the fields of physics, biology, human health, or artificial intelligence. Every time people think that everything has already been discovered, there occurs another breakthrough. However, it is impossible to predict specifically when and what it will be. Among the most promising challenges on the border between science and our imaginations, is an exploration of our universe, and potential contact with an extra-terrestrial civilisation, better understanding of space, time, matter, and energy (including “dark matter” and “dark energy”) and, of course, the “unthinkable” potential of the human brain. It seems that what may never be discovered is scientific evidence of life after death. This is not found on the border between science and our fantasy (imagination), but on the border between science and faith.